PERAN KELOMPOK BATIK “BERKAH LESTARI” BAGI PEMBERDAYAAN PEREMPUAN DI DUSUN KARANGKULON, DESA WUKIRSARI, IMOGIRI, BANTUL, YOGYAKARTA - Riesta Mar’atul Azizah (Jurnal Sosiologi Reflektif, 2014)
One of women empowerment strategies in Bantul regency is realized through supporting the Micro, Small and Medium Enterprises (UKM).One success UKM is Batik Berkah Lestari, located in the hamlet of Karangkulon, Wukirsari Village, District Imogiri, Bantul. This study tends to determine the role of Berkah Lestari groupin empowering women in Karangkulon. This study uses the theory of AGIL (adaptation, goal attainment, integration, latency) of Talcott Parsons. Data are collected through: observation, interviews and documentation. The results of this study indicate that the Berkah Lestari is able to contribute to women in Karangkulon through four things: adaptation, members of the group can customize the group rules and the changing environment; achievement of objectives, activities Berkah Lestari focus to achieve common prosperity, not a personal interest; integration, open communication between members and administrators make Berkah Lestari can survive and exist up to now; maintenance pattern, promoting a sense of kinship among the members of Berkah Lestari so that members feel comfortable and far from conflct. The results are clearly seen from three aspects: the economic aspects, namely increasing women’s income compare toprevious occupation before joining the Berkah Lestari; political aspect, in which women of Karangkulon managed to form a group of batik to fiht for their interests withoutbeing inferior when talking to visitors of Berkah Lestari; socio-cultural aspects, where women are considered equal to men because they can perform multiple roles, as a good housewife as well as helping the family’s income. In empowering women, Berkah Lestari relied heavily on trust, openness, and sense of family relation among its members. However, there are some barriers faced by the Berkah Lestari,such as: marketing is still limited to a conventional way (word of mouth), online marketing is not optimally used as a result of the lack of training on the developmentof batik and how to use internet.